Design, Manufacturing and Testing of Biaxial Mechanical Travelling Pluviator. Issue 1 (June 2020) - Aldefae, Asad H.; Saleem, Hiba D.
Abstract: This paper includes design, manufacturing, operation and testing of a special device for preparation of granular or sandy soil (cohesionless soil) models that widely used as a part of the physical modelling in geotechnical engineering which is a main part of the civil engineering. To achieve a desired and uniform relative density of sandy soil models during preparation, air pluviation technique using pluviator is more suitable as the sand particles can be dandified through falling of sand grains from different heights and may even reaches to very dense state. Steel materials from local markets are used in the design of mechanical pluviator manufacturing. The mechanical pluviator consist of main steel frame, movable bench that can be moved up and down mechanically, crane lever to control on the pluviator container, pulleys and wheels. CPT tests are conducted at different prepared sandy models to investigate the skin resistance at different densities and the results shows great agreement. Different steel sections materials with different light steel plates which reduce the device weight available in the local markets were used in the manufacturing of the pluviator machine. The machine was provided by crane lever and gear box that can be controlled mechanically to achieve the desired height for the falling sand grains. The maximum height that can be attained is 120 cm and 40 cm is the minimum value. The machine contained also a v-shape container provided with 4 reels or pulleys that can be moved back and forth along two parallel steel tubes girders which the filled sandy model is located below it. The v shape container has two plate sides; the first one is fixed while the other is movable to achieve the desired opening depth or slot width and can be changed easily. The container with its carried frame can be controlled via mechanical rode that can be move up and down using multi-coil wire. The machine is verified using cone penetration test at results at different soil relative densities.